Graphene quantum dots: effect of size, composition and curvature on their assembly. Issue 29 (21st March 2017) - Elvati, Paolo; Baumeister, Elizabeth; Violi, Angela
Abstract : The enhanced configurational stability of graphene quantum dots in clusters. Abstract : Graphene Quantum Dots (GQDs) are a relatively new class of molecules that have ignited tremendous research interest due to their extraordinary and tunable optical, electrical, chemical and structural properties. In this work, we report a molecular-level elucidation of the key mechanisms and physical–chemical factors controlling the assembly and stability of nanostructures formed by GQDs in an aqueous environment, using molecular dynamics simulations. We observe the general tendency to form small aggregates and three recurring configurations, one of them with a single layer of water separating two GQDs. The type and characteristics of the structure are mostly determined by the hydrophobicity of the GQDs as well as the steric hindrance of the dangling groups. The composition of the terminal groups plays a key role in determining the configuration of the GQDs, which is also markedly affected by the formation of clusters. Notably, the aggregated GQDs assume strongly correlated shapes and, in some cases, display a radically different conformation distribution compared to single molecules. This cooperative effect prolongs the lifetime of the GQD configurations and can explain the observed persistence of chiral conformations that are only marginally more stable than their specular images.